KAJIAN LITERATUR FAKTOR PSIKOLOGIS TERHADAP PERFORMA DAN KESEJAHTERAAN ATLET - Rangga Raditya, Bagus; Pudjijuniarto; Sudijandoko, Andun; Saputra, Yudi Dwi (JURNAL ILMU KEOLAHRAGAAN, 2025)
The issue of athletes' mental health is currently a serious concern for various groups. This study aims to analyze psychological factors on athletes' performance and well-being through a literature review. The method used was a Systematic Literature Review (SLR) by examining articles from Google Scholar, Scopus, and ResearchGate. Selection was based on inclusion criteria (articles from 2015–2025, relevant to sports psychology, full-text) and exclusion criteria (proceedings, theses/dissertations, duplicates). From this process, ten main articles were obtained and analyzed using thematic synthesis. The results showed that intrinsic motivation, self-efficacy, and mental toughness contributed positively to performance improvement, while anxiety and burnout had a negative impact on concentration and achievement. Social support, mindfulness, and integrated psychological interventions were also found to maintain athletes' mental well-being. Athletes' success is influenced not only by physical aspects but also by psychological resilience and external support. Practitioners are advised to integrate mental training, while further research needs to explore technology-based interventions.